2012
DOI: 10.1055/s-0032-1329988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antihypertensive Drugs on Angiotensinase Activities in the Testis of Spontaneously Hypertensive Rats

Abstract: Sexual dysfunction is a frequent adverse effect during antihypertensive therapy. However, the mechanisms responsible for these effects are not well understood. The renin-angiotensin system has been identified in testis where it may play a role in testicular function and be involved in the detrimental effects of antihypertensive drugs. Therefore, our objective was to compare the influence of captopril and propranolol on plasma testosterone levels and on hydrolyzing angiotensin's enzymes (angiotensinases) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…However, propranolol at the dose used did not modify SBP either in hypertensive animals as previously reported [13] or in WKY rats (fig. 2).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, propranolol at the dose used did not modify SBP either in hypertensive animals as previously reported [13] or in WKY rats (fig. 2).…”
Section: Discussionsupporting
confidence: 80%
“…However, SBP was unaffected after propranolol treatment either in WKY or in SHR [13]. SBP was significantly higher in the control (p < 0.001), L -NAME- (p < 0.05) and propranolol- (p < 0.001) treated SHR groups than in the WKY group (fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A local renin-angiotensin system (RAS) has been clearly established in testis which may participate in male reproductive functions [ 9 , 10 , 11 ]. It has been suggested that Ang II-metabolizing activity (glutamyl aminopeptidase, GluAP) may be influenced by dietary fatty acids composition and cholesterol content during early mice development [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These alterations, depending on the degree of fatty acid saturation, are related to changes in the systemic or local renin-angiotensin systems (RAS) [5][6][7][8][9][10]. The activation of the RAS participates in the development of MetS, heart failure [11], and pathophysiology of hypertension [4,7,[12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Within these local RAS, the type of fatty acids consumed with the diet allows modifying various enzymes of the aminopeptidase We hypothesized that the inclusion of MUFA in the diet could be a preventive dietary factor for reducing the activation of the RAS pathway through angiotensinases and maintaining the functional integrity of cardiovascular structures.…”
Section: Introductionmentioning
confidence: 99%